TRUST AS A FACTOR OF AN ORGANISATION’S EFFECTIVENESS - Prokopovych, Evgen; Idobaeva, Alla (PSYCHOLOGICAL JOURNAL, 2020)
The article presents the results of the theoretical and empirical study on the phenomena of trust and corporate culture. Based on the theoretical analysis and the study results, we concluded that trust, psychological atmosphere and organizational culture are not only significant factors in an enterprise’s economic efficiency, but also the main indicators of its psychological effectiveness. An organization’s psychological effectiveness is understood as its staff’s ability and willingness to perform their assigned tasks, including their willingness to make necessary or inevitable changes in the external and internal environment of the organization. Corporate culture and trust are integrative indicators of an organization’s psychological effectiveness, since, in addition to psychological relationships, they also include the regulatory system of decision-making and organizational behaviour.